2013
DOI: 10.2147/ijnrd.s45466
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis in patients with inflammatory bowel disease in the community

Abstract: BackgroundInflammatory bowel disease (IBD) has been associated with renal stone formation. The objective of this study was to determine prospectively the prevalence of nephrolithiasis in a community-based population of patients with IBD and to analyze factors associated with renal calculus formation.MethodsScreening renal ultrasound was performed in a well characterized cohort of patients seen between 2009 and 2012 at an IBD clinic. We enrolled 168 patients, including 93 with Crohn’s disease and 75 with ulcera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 12 publications
2
39
0
2
Order By: Relevance
“…In contrast, none of these factors were associated with urolithiasis in our study. A recent study conducted in Brazil by Cury et al [19] showed that ileocolonic disease is a significant risk factor for renal calculi. These data suggest that the extent of disease contributes to nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, none of these factors were associated with urolithiasis in our study. A recent study conducted in Brazil by Cury et al [19] showed that ileocolonic disease is a significant risk factor for renal calculi. These data suggest that the extent of disease contributes to nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that patients with persistent active disease are given immunosuppressants more frequently than in those in the inactive state. This might have been due to the number of episodes of diarrhea, which could have led to a decrease in urinary volume and greater urinary electrolyte loss due to dehydration [19]. Therefore, decreased absorption and diminished urinary excretion of citrate and magnesium, which normally act as inhibitors of calcium oxalate crystallization, contribute to stone formation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some patients suffering from recurrent oxalate calculi, present malabsorption of ascorbate, which in the gut is converted in oxalate, leads to a further increased oxaluria; another, even less frequent, cause of renal stone formation is the loss of the bacterium Oxalobacter formigenes (anaerobic bacterium that plays a key role in oxalate degradation), that occurs after extensive small bowel resection (37,38).…”
Section: Renal Involvementmentioning
confidence: 99%
“…2 In the case of IBD patients, even when stone symptoms are present, they may be overshadowed by concurrent bowel symptoms, increasing the chance of missed detection. These patients may also be unaware that their IBD puts them at risk of nephrolithiasis.…”
Section: Commentmentioning
confidence: 99%
“…Urolithiasis is one such manifestation that is present in upward of 25%-30% of patients with IBD. 1,2 Metabolic derangements, chronic dehydration, primary malabsorption, and malabsorption secondary to bowel resection are factors associated with IBD that predispose these patients to urinary calculi formation. [3][4][5] As a result, they often present with multiple stones and are at risk of stone recurrence if the underlying causes are not adequately addressed.…”
mentioning
confidence: 99%